Pengaruh Citra Merek dan Periklanan terhadap Keputusan Pembelian Polis Asuransi - Dea Putri Amanda; Nuri Aslami (VISA: Journal of Vision and Ideas, 2021)
The purpose of this study was to determine the effect of brand image or brand image and advertising on insurance policy purchasing decisions made by insurance consumers. The results of the study state that the first is the influence of brand image or brand image factors on the purchase choice of insurance policy customers. second, that there is no effect of advertising on the choice to purchase an insurance policy. third, that there is a positive influence between brand image and the negative impact of advertising on insurance policy purchasing decisions.